The preventive effect of exogenous adenosine triphosphate on methanol-induced cardiotoxicity in rats - Resit Coskun; Aziz Inan Celik; Muharrem Said COSGUN; Renad Mammadov (Universidade de São Paulo, 2023)
Abstract Exposure to methanol can cause serious consequences such as permanent visual disturbances and death. The heart tissue is highly vulnerable to ATP deficiency. Our study aimed to investigate whether exogenous ATP administration may alleviate methanol-induced ATP deficiency and subsequent oxidative damage in rat heart tissue. A total of 30 rats were divided into equal five groups; Healthy Group (HG), Methotrexate (MXG), Methanol (MeOH), Methotrexate+Methanol (MXM), and Methotrexate+Methanol+ATP (MMA) groups. We inhibited tetrahydrofolate synthesis by methotrexate to induce methanol toxicity. Methotrexate was administered to MXG, MXM, and MMA group animals for seven days with a catheter directly to the stomach at a 0,3 mg/kg dose per day. At the end of this period, % 20 methanol at a dose of 3 g/kg was administered to MeOH, MMA and MXM group animals. Immediately after methanol application, MMA group animals were injected with ATP at a 4 mg/kg dose intraperitoneally. Blood samples and heart tissues were used for biochemical analysis and histopathological examination. Co-exposure to methanol and methotrexate substantially exacerbated cardiac damage, indicating the potent cardiotoxic effects of methanol. However, the administration of exogenous ATP to MMA group animals brought biochemical oxidative damage parameters and histopathological findings closer to HG.